I Do Not Buy Your Story! Understanding the Limits of Storytelling in Corporate Social Responsibility Communication - Lukas Krenz; Laura Marie Edinger-Schons; Sabrina Scheidler; Sankar Sen; Jan Wieseke (Psychology & Marketing, 2025)
Storytelling is a popular approach for communicating corporate social responsibility (CSR) activities. However, its effectiveness in this context remains underexplored. This paper investigates the potential downsides of storytelling in CSR communication, particularly its capacity to backfire by evoking consumer skepticism. Across two field experiments ( n ₁ = 823; n ₂ = 5411) with actual customers of a global retailer and one scenario-based experiment ( n ₃ = 1175), we demonstrate that storytelling, compared to an expository message format, can increase perceptions of manipulative intent and extrinsic attributions regarding a company's CSR efforts. These effects, in turn, reduce consumer loyalty and purchase behavior. Notably, this backfire effect is pronounced in communication about peripheral CSR activities (e.g., philanthropy) but not embedded CSR initiatives (e.g., employee-focused programs). By integrating theories of persuasion knowledge, storytelling, and social-relational framing, our findings challenge the assumption of storytelling's universal efficacy and highlight its context-dependent outcomes. We offer actionable insights for CSR and communication managers to align storytelling strategies with CSR type and consumer expectations.
Keywords: 650; corporate social responsibility (CSR) communication; CSR embeddedness; extrinsic attributions; persuasion knowledge; storytelling